Irisin immunoreactivity in hematological malignancies - Yardim, M.; Kuloglu, T.; Ozercan, I. H.; Kenanoglu, O.; Aydin, S. (Wiley-Blackwell, 2016)
[Abstract Not Available]
41st FEBS Congress on Molecular and Systems Biology for a Better Life -- SEP 03-08, 2016 -- Kusadasi, TURKEY